Direct synthesis of monolayer gold nanoparticles on epoxy based photoresist by photoreduction and application to surface-enhanced Raman sensing. (1st January 2021) - Chen, Yi-Jui; Chang, Wen-Huei; Li, Chia-Ying; Chiu, Yi-Chun; Huang, Chih-Chia; Lin, Chun-Hung
Abstract: The photoreduction method is a potential method in terms of simplification, speed and cost of the process. This paper presents a simple and novel method for the direct synthesis of a gold nanoparticle monolayer with a droplet of gold precursor on the surface of SU-8 under UV exposure. Photoreduction ability on different polymer surfaces with various photoinitiator concentrations was investigated. The horizontal and vertical distributions of reduced nanoparticles were examined by using a scanning electron microscope and a transmission electron microscope, and crystalline property was verified through energy dispersive X-ray spectroscopy. The influence of SU-8 initial curing time and reduction repetition times on nanoparticle sizes and densities was investigated. The same photoreduction process is applicable to the surface of SU-8 nanostructures. The use of SU-8 nanopillars as a photoreduction substrate can provide a high specific surface area for improving the density of hot spots in the application of surface-enhanced Raman spectroscopy. Graphical abstract: Unlabelled Image Highlights: Monolayer gold nanoparticles are synthesized by shining UV over HAuCl4 droplet on SU-8. The epoxy resin together with the photoinitiator play key roles in photoreduction. Particle size and density are adjustable by curing time and repeated reduction. R6G Raman signal on SU-8 nanopillars is five times stronger than on SU-8 films.